Factors associated with disordered eating among primary school children in Selangor, Malaysia - Chong, Lin Siew (2016)
The prevalence of disordered eating is on the rise among children. This study aimed to determine the prevalence of disordered eating and the associations between sociodemographic characteristics, pubertal development, body weight status, psychological factors, socio-cultural factors and behavioral factors with disordered eating among primary school children (aged 10 to 11 years) in Selangor. A total of 816 children (35.1% males and 64.9% females) from 12 randomly selected primary schools involved in this cross-sectional study. Children completed a set of selfadministered questionnaire on disordered eating, socio-demographic characteristics (sex, ethnicity, parental monthly income, parental education level), pubertal development, psychological factors (self-esteem, depression, health specific selfefficacy, body size satisfaction), socio-cultural factors (perceived pressure to lose weight, gain weight and increase muscle tone from parents, peers and media) and behavioral factors (meal skipping behaviors, snacking behaviors, fast food consumption, dietary intake, physical activity level). Their body weight and height were measured and body weight status was categorized based on WHO Growth Reference (2007). Multivariate logistic regression analysis was conducted to determine factors associated with disordered eating among the children. The prevalence of disordered eating was 30.8% [Males: 32.8% (95% CI: 27.3, 38.8); Females: 29.7% (95% CI: 25.8, 33.9)]. Older age children (10.7; 95% CI: 10.7, 10.8) reported higher prevalence of disordered eating than younger age children (10.5; 95% CI: 10.5, 10.6). Indian (39.9%; 95% CI: 29.3, 51.40) showed the highest prevalence of disordered eating, followed by Malay (33.6%; 95% CI: 29.7, 37.8) and Chinese (17.0%; 95% CI: 11.8, 23.8). Children who were in advanced and post-pubertal stage had the highest prevalence of disordered eating (44.6%; 95% CI: 33.0, 56.7). Those who consumed fast food at least once a week showed the highest prevalence of disordered eating (38.4%; 95% CI: 32.6, 44.5). Socio-cultural pressures to lose weight among children with disordered eating (32.4; 95% CI: 31.0, 33.8) was higher than those without disordered eating (27.6; 95% CI: 26.7, 28.4). No associations were found between sex, parental monthly income, parental education level, body weight status, self-esteem, depression, health specific self-efficacy, body size satisfaction, meal skipping behaviors, snacking behaviors, energy and macronutrient intakes, energy expenditure and physical activity level with disordered eating of the children. Factors that associated with disordered eating were being an Indian (OR = 2.048; 95% CI: 1.050, 3.995), perceived pressure to lose weight from parents, peers and media (OR = 1.035; 95% CI: 1.017, 1.053) and fast food consumption at least once a week (OR = 1.540; 95% CI: 1.098, 2.162) after age was controlled. In conclusion, one third of the children had disordered eating. After controlling for age, factors of disordered eating in both males and females were being an Indian, perceived pressure to lose weight from parents, peers and media and fast food consumption at least once a week. Future ethnic specific intervention programs on the prevention of disordered eating should be taken consideration of age, socio-cultural factors and fast food consumption.